2012
DOI: 10.5402/2012/569862
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype and Metabolic Disorders in Polycystic Ovary Syndrome

Abstract: The polycystic ovary syndrome (PCOS) is one of the most frequent endocrinopathies in women. Its incidence is assessed at 6–8% of the female population in the reproductive age. It is characterised by oligomenorrhea (Oligo), hyperandrogenism (HA), and the presence of polycystic ovaries (PCOs). Carbohydrate and lipid metabolism is being disturbed in many women with PCOS. The pathogenesis of PCOS is still unexplained. Following the main criteria of diagnosis (Rotterdam Consensus 2003), Dewailly, Welt and Pehlivano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
37
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 11 publications
(18 reference statements)
10
37
1
1
Order By: Relevance
“…group A [2]; other researchers have also reported the worst disturbances [3, 32]. In a study from Greece, IR was higher among groups A and B, but had the lowest levels among group C (HA + PCO), it was concluded that group C had the lowest risk of cardiovascular diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…group A [2]; other researchers have also reported the worst disturbances [3, 32]. In a study from Greece, IR was higher among groups A and B, but had the lowest levels among group C (HA + PCO), it was concluded that group C had the lowest risk of cardiovascular diseases [20].…”
Section: Discussionmentioning
confidence: 99%
“…It is a complex and intractable disorder with psychological (increased anxiety, depression and worsened quality of life), reproductive (infertility, hyperandrogenism and hirsutism) and metabolic manifestations [insulin resistance, impaired glucose tolerance, type 2 diabetes mellitus (T2DM) and adverse cardiovascular risk profiles] (3). Due to menstrual disorders, hyperandrogenism and persistent anovulation, PCOS is considered to be the main cause of infertility in women (4). An estimate of 50-70% of women with PCOS have insulin resistance (5).…”
Section: Introductionmentioning
confidence: 99%
“…Whether a balanced diet and a correct food processing can facilitate the right intake of phytates, however in many case a satisfying condition cannot be achieved in specific population sectors by these means. It is well known that, in agreement with the Rotterdam criteria, four different "discrete" phenotypes, or subsets, can be identified in PCOS women [31][32][33]. Therefore, we may allocate them in the following groups of subjects affected by two or three clinical and endocrine anomalies: The most common subset is the phenotype 1, with 60,2%, whereas the other groups showed respectively these frequencies: group 2 with 16,1%, 3 with 18,3%, and 4 with 5,4%.…”
Section: Balanced Diet For Improving Phytate Digestion and Dietary Sumentioning
confidence: 88%
“…Therefore, we may allocate them in the following groups of subjects affected by two or three clinical and endocrine anomalies: The most common subset is the phenotype 1, with 60,2%, whereas the other groups showed respectively these frequencies: group 2 with 16,1%, 3 with 18,3%, and 4 with 5,4%. [33]. In many of these subjects it may be necessary associating to a correct diet also the intake of dietary supplements containing inositol.…”
Section: Balanced Diet For Improving Phytate Digestion and Dietary Sumentioning
confidence: 99%